The influence of habitat fragmentation on helminth communities in rodent populations from a Brazilian Mountain Atlantic Forest. Issue 4 (24th July 2015) - Cardoso, T.S.; Simões, R.O.; Luque, J.L.F.; Maldonado, A.; Gentile, R.
Abstract: The influence of habitat structure on helminth communities of three sigomdontinae rodent species ( Akodon cursor, A. montensis and Oligoryzomys nigripes ) was investigated in forest fragments within an agricultural landscape in south-eastern Brazil. This is a pionner study correlating the occurrence of helminth species of rodent hosts with microhabitat characteristics. Rodents were collected from 12 fragments and in a continuous conserved area. Up to 13 nematode, three cestode and two trematode species were identified, and habitat fragmentation was found to have more influence on the helminth composition of O. nigripes compared to the other two rodent species. Fragmentation appeared to limit the development of some helminths' life cycles, e.g. with some species such as Trichofreitasia lenti, Protospirura numidica, Cysticercus fasciolaris and Avellaria sp., occurring mostly in areas with less anthropic impact. However, fragmentation did not seem to affect the life cycles of other dominant helminths, such as the trematode Canaania obesa, the nematodes Stilestrongylus lanfrediae, S. eta and S. aculeata, and the cestode Rodentolepis akodontis. The helminth community structure followed a nested pattern of distribution in A. montensis and O. nigripes . Stilestrongylus lanfrediae seemed to be more associated with dense understorey, C. obesa with open canopy and dense understorey, and Guerrerostrongylus zetta with organic matter on the ground. Their presence in each area may be explained by aspects of their life cycles that take place in the external environment outside the host.